A Review of Oxygen Physiology and Appropriate Management of Oxygen Levels in Premature Neonates. (April 2018) - Kayton, Allyson; Timoney, Paula; Vargo, Lyn; Perez, Jose A.
Abstract : Background: Although oxygen is the most widely used therapeutic agent in neonatal care, optimal oxygen management remains uncertain. Purpose: We reviewed oxygen physiology and balance, key studies evaluating oxygen saturation targets, and strategies for oxygen use in the neonatal intensive care unit. Results: Oxygen is a potent vasodilator involved in the transition at birth to breathing. Supplemental oxygen is administered to reverse/prevent hypoxia; however, excessive oxygen can be toxic owing to the formation of reactive oxygen species. Current neonatal resuscitation guidelines recommend using room air for term infants in need of support, with titration to achieve oxygen saturation levels similar to uncompromised term infants. In premature infants, targeting a higher oxygen saturation range (eg, 91%-95%) may be safer than targeting a lower range (eg, 85%-89%), but more evidence is needed. In combined analyses, lower oxygen saturation levels increased mortality, suggesting that the higher target may be safer, but higher targets are associated with an increased risk of developing disorders of oxidative stress. Implications for Practice: Need for supplemental oxygen should be assessed according to the American Heart Association guidelines. If appropriate, oxygen should be administered using room air, with the goal of preventing hypoxia and avoiding hyperoxia. Use of oximeter alarms may help achieve this goal. Pulmonary vasodilators may improve oxygenation and reduce supplemental oxygen requirements. Implications for Research: Implementation of wider target ranges for oxygen saturation may be more practical and lead to improved outcomes; however, controlled trials are necessary to determine the impact on mortality and disability.